2005
DOI: 10.3168/jds.s0022-0302(05)72706-5
|View full text |Cite
|
Sign up to set email alerts
|

Invited Review: Prevalence of Shiga Toxin-Producing Escherichia coli in Dairy Cattle and Their Products

Abstract: The main objective of this review was to assess the role of dairy cattle and their products in human infections with Shiga toxin-producing Escherichia coli (STEC). A large number of STEC strains (e.g., members of the serogroups O26, O91, O103, O111, O118, O145, and O166) have caused major outbreaks and sporadic cases of human illnesses that have ranged from mild diarrhea to the life-threatening hemolytic uremic syndrome. These illnesses were traced to O157 and non-O157 STEC. In most cases, STEC infection was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
124
3
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 207 publications
(137 citation statements)
references
References 81 publications
6
124
3
4
Order By: Relevance
“…The prevalence of O157 E. coli as revealed in this study is inclined with the previous report of Hussein and Sakuma (2005).…”
Section: Discussioncontrasting
confidence: 78%
“…The prevalence of O157 E. coli as revealed in this study is inclined with the previous report of Hussein and Sakuma (2005).…”
Section: Discussioncontrasting
confidence: 78%
“…This proportion is in parallel with previous studies except the researchers conducted in South Africa. The differences between the results may be due to cultivation method, sample size and resource, geographical region, season and degree of dispersion of E. coli O157: H7 infections in the region [14] .…”
Section: Discussionmentioning
confidence: 99%
“…However, samples were collected in winter and spring months. It was reported that in ruminants the prevalence of Escherichia coli O157:H7 is the highest in summer months and decreases in winter months 6,26 . Pathogenic STEC strains produce toxins that cause human illnesses and can produce other virulence factors that may increase the severity of illnesses.…”
Section: Discussionmentioning
confidence: 99%